2018
DOI: 10.1002/jcp.26928
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Long non‐coding RNA LINC00152 promotes cell growth and invasion of papillary thyroid carcinoma by regulating the miR‐497/BDNF axis

Abstract: Long intergenic non-coding RNA 152 (LINC00152) was reported to be tightly linked to tumorigenesis and progression in multiple cancers. However, its biological role and modulatory mechanism in papillary thyroid carcinoma (PTC) has not been elucidated. In this study, we determined the expression levels of LINC00152 in PTC tissues and cell lines by quantitative real time polymerase chain reaction (qRT-PCR). Cell proliferation, colony formation, migration, and invasion were measured by a Cell Counting Kit-8 assay,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…In our present study, publicly available data and qRT-PCR results both uncovered that LINC00152 expression in CCA tissues was observably higher than that in corresponding non-tumor tissues, which implied the important role of LINC00152 in CCA progression. LINC00152 was reported upregulated in various cancers, promoting cancer cell proliferation and migration [20][21][22][23][24][25][26][27][28][29][30][31][32]. Nevertheless, the possible role of LINC00152 in CCA is still undocumented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our present study, publicly available data and qRT-PCR results both uncovered that LINC00152 expression in CCA tissues was observably higher than that in corresponding non-tumor tissues, which implied the important role of LINC00152 in CCA progression. LINC00152 was reported upregulated in various cancers, promoting cancer cell proliferation and migration [20][21][22][23][24][25][26][27][28][29][30][31][32]. Nevertheless, the possible role of LINC00152 in CCA is still undocumented.…”
Section: Discussionmentioning
confidence: 99%
“…Long intergenic non-coding RNA 152 (LINC00152), a 828-bp lncRNA that maps to chromosome 2p11.2, was initially found to be differentially hypomethylated in hepatocarcinogenesis [19]. Continuously, LINC00152 have exhibited carcinogenic properties in a variety of cancers, including gastric cancer, hepatocellular carcinoma, colon cancer, gallbladder cancer, lung adenocarcinoma, breast cancer, nonsmall-cell lung cancer, papillary thyroid carcinoma, tongue squamous cell carcinoma, glioblastoma and ovarian cancer [20][21][22][23][24][25][26][27][28][29][30][31][32]. However, the expression pattern, biological function, and underlying mechanism of LINC00152 in human CCA remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNA LINC00152, which is located in human Chr2p11.2, is reported to be upregulated in several types of cancer. In thyroid cancer, LINC00152 acts as a miR-497 'sponge', downregulating its downstream target, brain-derived neurotrophic factor (BDNF), to promote the proliferation and invasion of papillary thyroid cancer cells (71). In multiple myeloma, LINC00152 acts as an oncogene and regulates cell growth by targeting miR-497 expression (72).…”
Section: Epigeneticsmentioning
confidence: 99%
“…Recently, accumulating articles revealed that one potential function of lncRNAs was to directly interact with miRNAs as a sponge and regulate their expression and activity [10]. For example, LINC00152 promotes cell growth and invasion of papillary thyroid carcinoma by regulating the miR‐497/BDNF axis [11]. However, the functions of lncRNA on miRNAs in the pathogenesis of NB has not been described.…”
Section: Introductionmentioning
confidence: 99%